Chorioamnionitis caused by Serratia marcescens in a healthy pregnant woman with preterm premature rupture of membranes: A rare case report and review of the literature. (April 2017) - Erenberg, Miriam; Yagel, Yael; Press, Fernanda; Weintraub, Adi Y.
Abstract: The incidence of chorioamnionitis varies widely. The highest incidence is reported in preterm deliveries. Among preterm deliveries, chorioamnionitis usually occurs after preterm premature rupture of membranes (PPROM). To date, only five cases of chorioamnionitis due to Serratia marcescens were reported. Here we present a case of a pregnant woman with chorioamnionitis due to Serratia marcescens who delivered a premature neonate at 28 weeks and four days of gestation. We also conducted a review of the literature in order to identify and characterize the clinical presentation and outcomes of this rare infection. A 36 year old female (gravida 9, para 6) was admitted with cervical effacement of 16 mm and intact membranes at gestational age of 25 weeks and five days. One week following her admission PPROM was noticed. Treatment with the standard antibiotic regimen for PPROM was initiated. Thirteen days after the diagnosis of PPROM (28 weeks and four days) she developed chills, abdominal pain, sub febrile fever, tachycardia, leukocytosis and fetal tachycardia, and a clinical diagnosis of chorioamnionitis was made. An urgent CS was performed. In the first post-operative day the patient developed surgical sight infection. Cultures obtained from the purulent discharge of the wound, as well as cultures from the placenta and uterine cavity that were obtained during surgery grew Serratia marcescens. The patient was treated with Meropenem for six days, with a good clinical response. We present a rare case of nosocomialy acquired Serratia marcescens chorioamnionitis in a patient with PPROM. This case emphasizes the need for good infection control measures. Our favorable outcome together with the scares reports in the literature, add insight into this type of rare infection.